PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN (Studi Pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank Semarang ) - Khoirul Khamdi, 11.05.51.0111; Soliha, Euis (Students Journal of Economic and Management, 2016)
This study on the effect of product quality, brand image and perception of the price of the purchase decision process latptop Toshiba. The data used in this research is the primary data, with the questionnaire as a research instrument, which is then processed by calculation SPSS (Statistical Product and Solutions) version 16. The population in this study is the Faculty of Economics and Business, which uses Toshiba laptop in the University Stikubank Unisbank Semarang , which amounted to 100 respondents. The sampling technique in this study using purposive sampling, that the sampling deliberate in accordance with the requirements of sample is required. The analysis tool used is multiple linear regression. The results showed that there are significant positive and not significant between the quality of the product to the purchase decision process. There is a significant positive effect between the brand image of the purchase decision process. There is a significant positive effect between the perception of the price of the purchase decision process. Keywords: Quality Product, Brand Image, Perceived Price, Purchase Decision